Insect pathogenicity in plant-beneficial pseudomonads: phylogenetic distribution and comparative genomics - Flury, Pascale; Aellen, Nora; Ruffner, Beat; Péchy-Tarr, Maria; Fataar, Shakira; Metla, Zane; Dominguez-Ferreras, Ana; Bloemberg, Guido; Frey, Joachim; Goesmann, Alexander; Raaijmakers, Jos M; Duffy, Brion; et al. (The ISME Journal, 2016)
Bacteria of the genus Pseudomonas occupy diverse environments. The Pseudomonas fluorescens group is particularly well-known for its plant-beneficial properties including pathogen suppression. Recent observations that some strains of this group also cause lethal infections in insect larvae, however, point to a more versatile ecology of these bacteria. We show that 26 P. fluorescens group strains, isolated from three continents and covering three phylogenetically distinct sub-clades, exhibited different activities toward lepidopteran larvae, ranging from lethal to avirulent. All strains of sub-clade 1, which includes Pseudomonas chlororaphis and Pseudomonas protegens , were highly insecticidal regardless of their origin (animals, plants). Comparative genomics revealed that strains in this sub-clade possess specific traits allowing a switch between plant- and insect-associated lifestyles. We identified 90 genes unique to all highly insecticidal strains (sub-clade 1) and 117 genes common to all strains of sub-clade 1 and present in some moderately insecticidal strains of sub-clade 3. Mutational analysis of selected genes revealed the importance of chitinase C and phospholipase C in insect pathogenicity. The study provides insight into the genetic basis and phylogenetic distribution of traits defining insecticidal activity in plant-beneficial pseudomonads. Strains with potent dual activity against plant pathogens and herbivorous insects have great potential for use in integrated pest management for crops.